2005
DOI: 10.1142/s1088424605000915
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and properties of carboranylpyrroles

Abstract: Synthetic routes to mono-and di-carboranylpyrroles (1-5) bearing the carborane groups linked either directly to the 3-and/or 4-positions of the pyrrole ring or via one or two methylene spacers are described. Several X-ray structures of key intermediates are presented and discussed. Carboranylpyrroles can be cyclotetramerized to afford carboranylporphyrins in low to moderate yields, depending on the number of carborane cages and their linkage to the pyrrole ring. The best yields of porphyrin were obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…The beneficial influence on the overoxidation resistance enhancement of BH-containing molecules in the PPy material has been further proven by the work of Fabré and co-workers which has shown an enhanced overoxidation stability in PPy materials containing neutral BH-containing molecules, in this occasion bound to the PPy strands. Therefore, it has been demonstrated that borane and metallaborane anions disconnected from the PPy strands on the one hand and neutral carboranes connected to the PPy strands on the other produce unprecedented overoxidation resistance to PPy materials.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The beneficial influence on the overoxidation resistance enhancement of BH-containing molecules in the PPy material has been further proven by the work of Fabré and co-workers which has shown an enhanced overoxidation stability in PPy materials containing neutral BH-containing molecules, in this occasion bound to the PPy strands. Therefore, it has been demonstrated that borane and metallaborane anions disconnected from the PPy strands on the one hand and neutral carboranes connected to the PPy strands on the other produce unprecedented overoxidation resistance to PPy materials.…”
Section: Resultsmentioning
confidence: 91%
“…From previous works PPy materials doped with [1] or with derivatives of [1] -(Figure 1) have been found to be 300-500 mV more anodic resistant than PPy doped with conventional anions. More recently even a more overoxidation robust material was obtained by using the bulky borane derivatives of 42 The beneficial influence on the overoxidation resistance enhancement of BH-containing molecules in the PPy material has been further proven by the work of Fabre ´and coworkers [43][44][45] which has shown an enhanced overoxidation stability in PPy materials containing neutral BH-containing molecules, in this occasion bound to the PPy strands. Therefore, it has been demonstrated that borane and metallaborane anions disconnected from the PPy strands on the one hand and neutral carboranes connected to the PPy strands on the other produce unprecedented overoxidation resistance to PPy materials.…”
Section: Overoxidation Resistance Limit: Differences Between Ppy Mate...mentioning
confidence: 99%
“…In Scheme A porphyrin units are covalently linked to the electroactive monomer and electropolymerization yields a “double-cable” polymer. The electrochemical polymerization of monomers containing porphyrins has been reported for a number of CP monomers, such as thiophene, , bithiophene, terthiophene, pyrrole, ethynyl-aniline, EDOT, and fluorene monomers . Since the precursor porphyrin can be substituted by four electroactive units, electropolymerization can further lead to 2D or 3D networks upon electropolymerization, as depicted in Scheme B. , Porphyrins incorporated in 1D polymer wires (Scheme C) have also been reported: fibers were obtained, for example, by electropolymerization of zinc-5,15-dichloro-10-[4,4′-bipyridinium-hexafluorophosphate]porphyrinate .…”
Section: Electrosynthesis Of Functionalized Conducting Polymersmentioning
confidence: 96%
“…Furthermore, some carborane-containing molecules even fail to be successfully electropolymerized when the carborane groups are too close to the aromatic rings. [23,24,26,27] On the other hand, a wide range of structurally-modified π-conjugated oligomers have been designed, synthesized and polymerized to afford materials with specific properties (e.g. photovoltaic properties and controlled length of the main chain).…”
Section: Several Strategies For Incorporation Of Carboranes Into Polymentioning
confidence: 99%